Le souterrain médiéval de la Croix-Blanche à Sardon (Puy-de-Dôme) - Frédéric Surmely; Alban Horry; Franck Loiseau; Étienne Bachelet; Stéphane Brouillaud (Revue Archéologique du Centre de la France)
The tunnel at la Croix-Blanche was accidentally discovered by the owner-operator of the plot. A sounding was conducted. It showed the existence of a complex system, presumably linked to storage, comprising a surface silo, an underground room housing two storage pits and providing access to three underground galleries, whose development could not be fully recognized. A georadar investigation failed to detect these ducts from the surface. The dating of wood charcoal and ceramics is part of the period 11th-13th s.